Table Talk: Essays on Men and Manners - Hazlitt, William, 1778-1830 (Salt Lake City, UT : Project Gutenberg, 2002)
"Table Talk: Essays on Men and Manners" by William Hazlitt is a collection of essays published in two volumes beginning in April 1821. This acclaimed work explores topics including art, literature, and philosophy through Hazlitt's masterful familiar essay style. From reflections on painting that blend aesthetic theory with intimate memories of his late father, to philosophical meditations on genius and greatness, these essays showcase the English critic's personal voice and cultural insight. Considered by scholars as the pinnacle of Hazlitt's literary achievement. (This is an automatically generated summary.)
On the pleasure of painting -- On the past and future -- On genius and common sense -- Character of Cobbett -- On people with one idea -- On the ignorance of the learned -- The Indian jugglers -- On living to one's-self -- On thought and action -- On will-making -- On certain inconsistencies in Sir Joshua Reynolds's discourses -- On paradox and common-place -- On vulgarity and affectation -- On a landscape of Nicolas Poussin -- On Milton's sonnets -- On going a journey -- On coffee-house politicians -- On the aristocracy of letters -- On critism -- On great and little things -- On familiar style -- On effeminacy of character -- Why distant objects please -- On corporate bodies -- Whether actors ought to sit in the boxes? -- On the disadvantages of intellectual superiority -- On patronage and puffing -- On the knowledge of character -- On the picturesque and ideal -- On the fear of death.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Table-Talk
Release date is 2002-01-01
Produced by Christopher Hapka, and David Widger
Keywords: English essays